Investigation of the Biochemical and Ultrastructural Mechanisms Underlying the Antimicrobial Activity of Mimusops spp. Extracts: Antimicrobial activity of Mimusops spp. (Baghdad Science Journal, 2020)
Antibiotic resistance is the major growing threat facing the pharmacological treatment of bacterial infections. Therefore, bioprospecting the medicinal plants could provide potential sources for antimicrobial agents. Mimusops, the biggest and widely distributed plant genus of family Sapotaceae, is used in traditional medicines due to its promising pharmacological activities. This study was conducted to elucidate the antimicrobial effect of three unexplored Mimusops spp. (M. kummel, M. laurifolia and M. zeyheri). Furthermore, the mechanisms underlying such antibacterial activity were studied. The Mimusops leaf extracts revealed significant antibacterial activities against the five tested bacterial strains with a maximum inhibition zone diameter of 22.0 mm against B. subtilis compared with standard antibiotic ciprofloxacin. The minimal inhibitory and bactericidal concentration values against tested Gram-positive and Gram-negative bacterial strains ranged from 3.15-12.5 µg/ml. However, weak antifungal effect was recorded against Candida albicans with MIC value ˃25 µg/ml. The 1, 1-diphenyl-2-picrylhydrazyl (DPPH) assay showed that M. caffra was the best antioxidant (IC50=14.75±0.028 µg/ml), while M. laurifolia was the least one (IC50=34.22±0.014 µg/ml). The phenolics in plant leaves extracts were identified and quantified by high performance liquid chromatography (HPLC) which revealed the presence of seven phenolic acids and four flavonoids. The abundant phenolic compounds were rutin (5.216±0.067 mg/g dried wt.) and gallic acid (0.296±0.068 mg/g) followed by myricetin (0.317±0.091 mg/g) then kaempferol (0.113±0.049 mg/g) as flavonoids. The antibacterial mechanism of M. laurifolia extract, as a representative species, induces ultrastructural changes in the model bacterium Staphylococcus aureus with cell wall and plasma membrane lysis as revealed by transmission electron microscopy. Overall, Mimusops species (M. laurifolia, M. kummel and M. zeyheri) are promising natural alternative sources for antimicrobial agents.